KONSENTRASI DAN INTERVAL PEMBERIAN ASAM HUMAT TERHADAP PERTUMBUHAN BIBIT TANAMAN TEBU (Saccarum officinarum L.) PADA SISTEM BUDCHIPS - Selen Shintara Putri; Djoko Heru Pamungkas; Sri Widata (JURNAL ILMIAH AGROUST, 2018)
The aim of this research namely to know the Konsentrate and interval giving humic acid for growth of cane plant seeds (Saccarum Officinarum L). This is done at Sugar Factory Maduskismo PT. Rajawali Nusantara Indonesia (Persero), Padokan Village, Tirtonirmolo, Kasihan Sub, Bantul Regency, The research is done at march up to may. This research is arraged with RAKL desaign with two factor , first is konsentrate 4% (D1), 6% (D2), 8% (D3). The second factor is giving interval 15 days (I1), 30 days (I2), 45 days (I3). The variable which is used covers number of leaves, wide of leaves, groos weight of leaves, dry weight of analysis use varianty fingerprint (anova) and continued with the smallest real different test (BNT) with real leadder 5%. The result of giving humic acid show that there are interaction at stemdiameter variable, plant long, leaf long.